Measurement of the lund jet plane using charged particles in 13 TeV proton-proton collisions with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Helary, Louis; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; Mkrtchyan, Tigran; Napolitano, Fabrizio; Ott, Philipp; et al. (Physical review letters, 2020)
The prevalence of hadronic jets at the LHC requires that a deep understanding of jet formation and structure is achieved in order to reach the highest levels of experimental and theoretical precision. There have been many measurements of jet substructure at the LHC and previous colliders, but the targeted observables mix physical effects from various origins. Based on a recent proposal to factorize physical effects, this Letter presents a double-differential cross-section measurement of the Lund jet plane using 139 fb−1 of √s=13 TeV proton-proton collision data collected with the ATLAS detector using jets with transverse momentum above 675 GeV. The measurement uses charged particles to achieve a fine angular resolution and is corrected for acceptance and detector effects. Several parton shower Monte Carlo models are compared with the data. No single model is found to be in agreement with the measured data across the entire plane.
ATLAS Collaboration: G. Aad, V. Andrei, A.E. Bolz, M. Dunford, S. Franchino, L. Helary, M. Klassen, A. Krishnan, A. Kugel, T. Mkrtchyan, F. Napolitano, P.S. Ott, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 10.05.2021